Introgression despite protection: the case of native brown trout in Natura 2000 network in Italy - Splendiani, Andrea; Giovannotti, Massimo; Righi, Tommaso; Fioravanti, Tatiana; Cerioni, Paola Nisi; Lorenzoni, Massimo; Carosi, Antonella; La Porta, Gianandrea; Barucchi, Vincenzo Caputo (Conservation genetics, 2019)
Mediterranean brown trout is subject to several serious threats such as pollution, water abstraction, habitat alteration and especially genetic introgression with domestic strains used for stocking activities. Despite this latter issue has largely been debated by scientists, local managers and stakeholders for decades, official stocking practices with domestic trout still persists in several countries (Italy included), even if there are laws explicitly prohibiting introduction of organisms of non-local origin. Probably, the last opportunity to conserve native brown trout populations is represented by protected areas. Therefore, in the present study, we aimed to verify the role of the Nature 2000 network and a national park as valid tools to guarantee the survival of native brown trout in the Apennines. Partial mitochondrial DNA control region sequence analysis and genotyping of the locus LDH-C1 * and 11 microsatellites were used to investigate the genetic diversity of three rivers from central Italy. For all rivers investigated a temporal analysis of introgression was also carried out. The genetic diversity of three domestic stocks was included in the sampling design for comparison. The main results of this study indicated that: (i) the genetic diversity of brown trout in central Italy is very complex and (ii) its conservation is seriously threatened by genetic introgression phenomena still ongoing. The only samples showing no introgression or a decrease in genetic introgression were those isolated by the presence of natural and/or artificial barriers to fish movements rather than protected by inhabiting rivers within the Natura 2000 network. This observation prompts an important reflection on issues concerning fluvial continuity restoration and suggests that barrier removal should be undertaken with caution in order to avoid the concrete risk of domestic trout spreading that could promote additional loss of native brown trout biodiversity.